Non-Pathogenic bacteria in Bioremediation of Cr (VI) for decontamination of ground water: An Extensive Review: Life Sciences-Microbiology for Health Care - Subhadeep Ganguly; Smaranika Pattnaik (International Journal of Life Science and Pharma Research, 2022)
Cr(VI), one of the most common ground waters heavy metal contaminant due to its indiscriminateuse in different industries has become a matter of major environmental concern. So, it is desirable that remediation methods should be such that brings its level within the permissible limits before effluents are discharged. The methods should be cheap as well as eco-friendly. Nowadays, severalbiological remediation strategies are used by applying microorganisms for its removal involving biosorption and biotransformation. Biosorption is dependent on surface nature of the biosorbentswhereas biotransformations depend on the presence of reductants. The present review includes bioremediation strategies of Cr(VI) based on biosorption or biotransformation or both by non-pathogenic bacteria only.